Investigation of mental health condition among factory worker during covid pandemic–a cross-sectional study - Hassan, Irna Syahira; Abdul Razak, Nur Fazhilah; Zakaria, Junaidah; Sukadarin, Ezrin Hani (2023)
The coronavirus disease 2019 (COVID-19) was initially reported in December 2019 in Wuhan, China, after a cluster of unusual pneumonia cases. On March 11, 2020, the World Health Organization (WHO) declared the outbreak a pandemic. Many workplaces are affected by work-related psychosocial risks and stress, as well as the adverse health and economic implications. Workers have been challenged, stretched, and tested in ways they have never been before, as have pharmaceutical manufacturing workers’ mental health, as they are responsible for providing optimal medication manufacturing that aids in therapy, treatment, and patient life during COVID-19. This study is to assess the level of depression, anxiety, stress, and associated factors among factory workers during COVID-19. A crosssectional study was conducted using online surveys to assess workers’ mental health and related factors. The study involves 201 manufacturing workers from various departments. The data were collected using a questionnaire distributed via an online platform. The data collection instrument consists of three parts: (1) sociodemographic, (2) related factors associated with mental health conditions, and (3) the DASS-21 survey. This study found that most workers have normal mental health conditions. Depression and anxiety have a significant correlation with sociodemographic characteristics and organizational factors. Meanwhile, stress has a significant correlation with socioeconomic and organizational aspects. All three mental health conditions have a significant correlation with organizational factors such as working experiences (>6 years) and preparation for workflow management during COVID- 19, with p-values of 0.028 and 0.023, respectively. The study’s findings may assist authorities in establishing ways to diagnose mental distress early, thereby reducing mental or psychological disease among factory workers